Pengaruh Keterampilan Komunikasi Guru terhadap Motivasi Belajar Siswa - Desi Ratna Sari (JPT : Jurnal Pendidikan Tematik, 2024)
This study aims to analyze the effect of teacher communication skills on students' learning motivation in Elementary Schools. Good communication skills are considered a key factor in creating a conducive and interesting learning environment for students. This study uses a quantitative method with a survey approach. The study population consisted of fifth and sixth grade students in several Elementary Schools in the X City area. The sample was taken using a purposive sampling technique, involving 150 students who participated in filling out a questionnaire designed to measure teacher communication skills and students' learning motivation levels. The collected data were analyzed using descriptive and inferential statistics, including linear regression analysis to determine the relationship between the two variables. The results showed that there was a positive and significant effect between teacher communication skills and student learning motivation. The better the communication skills of teachers, the higher the level of student learning motivation. This study concludes that improving teacher communication skills can contribute to improving student learning motivation, so it is important for teachers to develop and train these skills in their teaching practices. These findings are expected to be a consideration for schools and educational institutions in designing training programs for teachers, as well as in efforts to create a better learning environment for students.